Teori-teori Tentang Jatuhnya Daulat Bani Umayyah dan Bangkitnya Daulat bani Abbasiah - M Atho Mudzhar (Al-Jami'ah: Journal of Islamic Studies, 1997)
The fall of Bani Umayya taken over Bani Abbasiya has been seen as an important moment by historians. This is because as the change of the ruler is not seen as the change of dynasty an sich. It is also seen as the change of social structure and ideology which became the turn of a new era in Islamic history. This paper sees that Abbasid dynasty did not come to rise through a coup. The fall of the old regime was not caused by the strength of the new system under Abbasid family but rather by the weakness of the old regime itself as a result of government inefficiency and the wide spread of corruption. The condition become worse due to family intrigues, tribal and religious sentiment, and the loss of intellectuals' support. These conditions contributed significantly to the fall of the Umayyad dynasty. On one hand. the wide support given by different groups to Abbasid regime, ensured that the rise of Abbasiya was a real revolution in its real meaning. It is like revolutions occurred in many modern countries. On the other hand, this support blurred Abbasid identity, for each supporting group felt that the revolution was their own. In this blurred identity, however, a new power was built by utilizing as many groups as possible. This was only the first episode of revolution, because the new dynasty did political selection that ended in the rise of the real owner of Abbasid dynasty.